2017
DOI: 10.1186/s12909-017-1075-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards healthy learning climates in postgraduate medical education: exploring the role of hospital-wide education committees

Abstract: BackgroundPostgraduate medical education prepares residents for delivery of high quality patient care during training as well as for later practice, which makes high quality residency training programs crucial to safeguard patient care. Healthy learning climates contribute to high quality postgraduate medical education. In several countries, modernization of postgraduate medical education has resulted in hospital-wide responsibilities for monitoring learning climates. This study investigates the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(24 reference statements)
1
5
0
3
Order By: Relevance
“…This survey corroborated findings that a positive learning environment can moderate the degree of impact between career calling and academic procrastination. Milou 59 mentioned that a harmonious learning environment contributes to high-quality medical education, a finding that was confirmed in this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This survey corroborated findings that a positive learning environment can moderate the degree of impact between career calling and academic procrastination. Milou 59 mentioned that a harmonious learning environment contributes to high-quality medical education, a finding that was confirmed in this study.…”
Section: Discussionsupporting
confidence: 84%
“…This theory states that people affected by the environment may engage in behaviors they would not otherwise participate in. 59 It could be interpreted that students’ decisions are influenced by the groups’ typical responses. 60 According to this theory, students would spend more time studying than usual when the learning environment encourages such behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the learning climate on outcomes of post-graduate medical education has been widely recognized [5, 9]. By evaluating the learning climate, we can get insights in how to improve student learning but also how to (re)design the learning environment and support faculty in their teaching role [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that a positive learning climate is a key factor for effective learning in different models of clinical, workplace based learning [3, 4]. Furthermore, the learning climate as experienced in postgraduate training programs has been linked to learning and clinical outcomes [57] as well as trainees’ long-term practice patterns in terms of quality and safety of patient care [8, 9]. In order to evaluate and improve the learning climate, valid and reliable instruments are needed [10].…”
Section: Introductionmentioning
confidence: 99%
“…35 A healthy learning environment has been associated with better residents' outcomes including satisfaction with training, the use of knowledge, and a professional identity development. 36,37 The importance of having a high-quality clinical learning environment stems from the knowledge that a high-quality learning environment will have a direct impact on workplace learning and, on the quality, and safety of the clinical care received by patients. Trainees exposed to a high-quality clinical learning environment will have been exposed to participation in the clinical care of patients in a supervised manner.…”
Section: Discussionmentioning
confidence: 99%